Chemically Resistant, Shapeable, and Conducting Metal‐Organic Gels and Aerogels Built from Dithiooxamidato Ligand. (10th March 2017) - Vallejo‐Sánchez, Daniel; Amo‐Ochoa, Pilar; Beobide, Garikoitz; Castillo, Oscar; Fröba, Michael; Hoffmann, Frank; Luque, Antonio; Ocón, Pilar; Pérez‐Yáñez, Sonia
Abstract : Metal‐organic gels (MOGs) appear as a blooming alternative to well‐known metal‐organic frameworks (MOFs). Porosity of MOGs has a microstructural origin and not strictly crystalline like in MOFs; therefore, gelation may provide porosity to any metal‐organic system, including those with interesting properties but without a porous crystalline structure. The easy and straightforward shaping of MOGs contrasts with the need of binders for MOFs. In this contribution, a series of MOGs based on the assembly of 1D‐coordination polymer nanofibers of formula [M(DTA)] n (M II : Ni, Cu, Pd; DTA: dithiooxamidato) are reported, in which properties such as porosity, chemical inertness, mechanical robustness, and stimuli‐responsive electrical conductivity are brought together. The strength of the MS bond confers an unusual chemical resistance, withstanding exposure to acids, alkalis, and mild oxidizing/reducing chemicals. Supercritical drying of MOGs provides ultralight metal‐organic aerogels (MOAs) with densities as low as 0.03 g cm −3 and plastic/brittle behavior depending on the nanofiber aspect ratio. Conductivity measurements reveal a semiconducting behavior (10 −12 to 10 −7 S cm −1 at 298 K) that can be improved by doping (10 −5 S cm −1 ). Moreover, it must be stressed that conductivity of MOAs reversibly increases (up to 10 −5 S cm −1 ) under the presence of acetic acid. Abstract : A series of metal‐organic gels and aerogels based on the assembly of 1D‐coordination polymer nanofibers of formula [M(DTA)] n (M II : Ni, Cu, Pd; DTA: dithiooxamidato) are reported, in which properties such as porosity, chemical inertness, mechanical robustness, and stimuli‐responsive electrical conductivity are brought together into an unprecedented material. Gelation approach provides a valuable tool to achieve metal‐organic mesoporous materials.